2005
DOI: 10.1002/rcm.1960
|View full text |Cite
|
Sign up to set email alerts
|

Serum protein profiling by miniaturized solid‐phase extraction and matrix‐assisted laser desorption/ionization mass spectrometry

Abstract: Serum profiling by matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) holds promise as a clinical tool for early diagnosis of cancer and other human diseases. Sample preparation is key to achieving reproducible and well-resolved signals in MALDI-MS; a prerequisite for translation of MALDI-MS based diagnostic methods to clinical applications. We have investigated a number of MALDI matrices and several miniaturized solid-phase extraction (SPE) methods for serum protein concentration and des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 29 publications
1
41
0
Order By: Relevance
“…The proteins were digested at 37°C overnight using trypsin (2 g enzyme/100 g protein), and the peptides were vacuum-dried to a volume of 20 l and acidified by adding formic acid. The tryptic peptides were desalted and concentrated on an Empore C18 extraction disk (3 M, St. Paul, MN) and reverse-phase POROS R3 (Perseptive Biosystems, Foster City, CA) packed in GELoader tips (Eppendorf, Hamburg, Germany) using a modified version of the previously described StageTips (14,21,22).…”
Section: Cell Culture and Stable Isotopic Labeling By Amino Acids In mentioning
confidence: 99%
“…The proteins were digested at 37°C overnight using trypsin (2 g enzyme/100 g protein), and the peptides were vacuum-dried to a volume of 20 l and acidified by adding formic acid. The tryptic peptides were desalted and concentrated on an Empore C18 extraction disk (3 M, St. Paul, MN) and reverse-phase POROS R3 (Perseptive Biosystems, Foster City, CA) packed in GELoader tips (Eppendorf, Hamburg, Germany) using a modified version of the previously described StageTips (14,21,22).…”
Section: Cell Culture and Stable Isotopic Labeling By Amino Acids In mentioning
confidence: 99%
“…However, there have been concerns about the reproducibility and coverage of these techniques. MALDI-MS profiling of serum/ plasma proteins or peptides usually requires SPE pretreatment or pre-enrichment with functionalized beads or particles [59,60,[79][80][81][82]. Numerous studies have reported the use of SELDI-TOF-MS with different functional ProteinChips for disease detection mainly based on distinct proteomic patterns [83][84][85][86][87].…”
Section: Quantitative Analysis and Profilingmentioning
confidence: 99%
“…For example, one study used solid-phase extraction and MALDI-TOF MS (25 ). In this study, 1 serum sample was prepared 8 times with C8 material and eluted directly onto the MALDI target.…”
Section: Reproducibility In Maldi Protein Profilingmentioning
confidence: 99%